The Use of Puzzle Learning Media to Increase Learning Motivation of Class XI Students on Tissue Structure and Function Material - Nur Januarti, Aulia; Yani, Indri; Nefoseno, Hedi (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2024)
Background: Learning motivation is a state of individual willingness or enthusiasm in planning and doing something in order to achieve predetermined goals. There are two objectives of this class action research, including to find out how to increase the motivation of students in class XI IPA 5 in the biology learning process of tissue structure and function material using puzzles as learning media, and to find out the implementation of the learning process of tissue structure and function that applies puzzle learning media in class XI IPA 5. Method: This study used class action research with the research subjects, namely 31 students of class XI IPA 5 SMA Negeri 9 Bogor City. There are two cycles with 4JP x 45 minutes for each research cycle. the instruments used in this study include a learning motivation questionnaire of 30 statements and a response questionnaire containing 10 statements for puzzle learning media based on a Likert scale. Results: Based on the data obtained regarding learning motivation by applying puzzle learning media, it is known that the average value of student motivation at the pre-cycle stage is 67%, the average value at the first cycle stage is 73%, and at the second cycle stage is 75%. The three average values are in the